An eleven year old boy with pain abdomen and early morning neuroparalytic syndrome. (August 2016) - Sharma, Milap; Kalia, Shaurya; Sharma, Seema
Abstract: An 11 year old boy presented with pain abdomen and tenderness all over body when he got up from sleep early in the morning and subsequently had one vomiting after 30 min. He had no other significant past medical history. The child was shifted to nearby health facility where he was managed as a case of acute abdomen on the basis of suggestive history and clinical findings. Within 2 h after the onset of clinical features suggestive of acute abdomen the patient went on to develop marked ptosis and flaccid quadriplegia. The young boy underwent a sequence of clinical tests which were noncontributory. Based on the clinical picture, a differential diagnosis of hypokalemic paralysis, botulism, Miller Fischer syndrome and EMNS were considered. Through exclusion, the most probable diagnosis for the symptoms was elapid envenomation hence he was started on anti-snake venom (ASV) with working diagnosis of EMNS. Within 2 h, he began to show improvement. This recovery with ASV suggests the possibility of elapid envenomation. Highlights: Envenomation by krait bite causes negligible local swelling or pain. Marked muscle paralysis associated with pain abdomen helps in making the diagnosis. Good history record and examination are the key factors to diagnose EMNS. To administer ASV is the most important decision in management of the patient.